Time course of restenosis with "black hole" on intravascular ultrasound after implantation of platinum–chromium everolimus-eluting stent: Assessment using optical frequency-domain imaging. Issue 3 (March 2018) - Kikuchi, Shinnosuke; Morita, Yukiko; Kanna, Masahiko; Dejima, Toru; Nakayama, Mina; Okajima, Yuichi; Hibi, Kiyoshi; Kimura, Kazuo; Tamura, Kouichi
Abstract: Management of in-stent restenosis (ISR) remains challenging even in the drug-eluting stent era. We report the case of a Japanese female with repeated ISR after primary percutaneous coronary intervention (PCI) for acute coronary syndrome. We observed ISR tissue with "black hole" on intravascular ultrasound, which appeared to be heterogeneous tissue on optical frequency-domain imaging (OFDI). Paclitaxel-coated balloon dilatation of the ISR lesion with "black hole" was ineffective. The morphological assessment of ISR tissue using OFDI might be important to treat ISR lesions by PCI. OFDI is a novel tool to observe the difference in the in-stent tissue characteristics. <Learning objective: In-stent restenosis (ISR) remains a clinical problem even in the drug-eluting stent (DES) era. The morphological assessment of ISR tissue using optical frequency-domain imaging (i.e. homogeneous, heterogeneous, and layered types) might be important to treat ISR lesions by percutaneous coronary intervention since the reaction to DES and drug-coating balloon seems to be different according to the in-stent tissue characteristics.>